2020
DOI: 10.1101/2020.08.19.257212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated environmental and genomic analysis reveals the drivers of local adaptation in African indigenous chickens

Abstract: Elucidating the genetic basis of environmental adaptation in indigenous livestock populations has important implications for sustainable breeding improvement. It requires a detailed untangling of relevant environmental pressures and fine resolution detection of genomic signatures of selection associated with these environmental parameters. Here, we uniquely employed an integrative approach, combining Ecological Niche Modelling (ENM) with (i) genome-wide analyses of positive signatures of selection (SSA) and (i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…The protein encoded by SDK1 is a member of the immunoglobulin superfamily and is highly expressed in artery-aorta and artery-tibial tissues (GTEx; Lonsdale et al 2013 ) (it is not present in the Sheep Gene Expression Atlas). SNPs near/in this gene were previously associated with low oxygen saturation in humans from Ethiopian high-altitude regions ( Alkorta-Aranburu et al 2012 ) and it was identified as a candidate for high altitude/low temperature adaptation in chickens sampled across Ethiopia ( Gheyas et al 2020 ). It has been associated with a wide range of phenotypes/conditions in humans, including retinal development, brain activity and certain cancers, and with several other traits in livestock, including feed conversion rate in cattle ( Barendse et al 2007 ), coat color in goats ( Nazari-Ghadikolaei et al 2018 ) and meat quality of pork (juiciness, intramuscular fat) ( Ji et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by SDK1 is a member of the immunoglobulin superfamily and is highly expressed in artery-aorta and artery-tibial tissues (GTEx; Lonsdale et al 2013 ) (it is not present in the Sheep Gene Expression Atlas). SNPs near/in this gene were previously associated with low oxygen saturation in humans from Ethiopian high-altitude regions ( Alkorta-Aranburu et al 2012 ) and it was identified as a candidate for high altitude/low temperature adaptation in chickens sampled across Ethiopia ( Gheyas et al 2020 ). It has been associated with a wide range of phenotypes/conditions in humans, including retinal development, brain activity and certain cancers, and with several other traits in livestock, including feed conversion rate in cattle ( Barendse et al 2007 ), coat color in goats ( Nazari-Ghadikolaei et al 2018 ) and meat quality of pork (juiciness, intramuscular fat) ( Ji et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological variables vary in terms of their influences on organisms as inducers of local adaptation. Knowledge of ecological factors responsible for adaptive variation should be the first step to design selective breeding programs on indigenous livestock, plan crossbreeding with improved genotypes, or introduce new genotypes from a different environment (Fleming et al, 2017;Bettridge et al, 2018;Birhanu et al, 2021;Gheyas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For every population, a single geographic coordinate was taken at the center of the village during sampling of chickens. Coordinates from nine additional grids (1.44 km 2 ), covering a total of 12.96 km 2 , were then drawn around a recorded location and extracted using Google Earth Pro v 7.3.2 to ensure high representation of environmental variability affecting the population ( Gheyas et al, 2021 ). This way the total number of “presence” or “occurrence” points used in SDMs for the 26 sample populations comprised 260 coordinates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is considered highly probable that these traits are not encoded by single major genes but are the result of the interaction of multiple genes [ 101 ], thus it could also be highly desirable to be incorporated into the development of high-performance IC for the tropics. For instance, recent evidence revealed some genomic regions under positive selection which are associated with water scarcity, scavenging challenges, feeding behavior, and altitude-induced stresses from a population of 245 Ethiopian IC selected from 34 different agro-ecological zones [ 108 ]. Despite the increased awareness about the importance of indigenous animal breeds, which includes their long history of adaptation to extreme habitats, little effort has been done to harness the genetic potential of African IC ecotypes in general.…”
Section: Future Management and Breeding Plan For Developing Chicken Breeding In East Africamentioning
confidence: 99%